Trade Policies, Exchange Rate and Developing Country’s Real Sector Export Performance - Edeme, Richardson Kojo; Nkalu, Nelson C.; Emecheta, Chisom; Ugwu, Sam (International Journal of Economics and Financial Issues, 2017)
For developing countries like Nigeria, empirical evidence have shown they are faced with policy management challenge because they are mostly involved in the production and export of primary products which is often characterized by unfavourable terms of trade. The essence of this study therefore is to ascertain if trade and exchange rate policies complement each other in stimulating non-oil exports, especially the agricultural and manufacturing sectors, using both aggregated and disaggregated approach. Empirical results suggest that the various exchange rate regimes in Nigeria have not produced the desired result that accentuates export performance. Results reveal that imported input and real world income promote export performance of the entire real sector, while terms of trade has insignificant impact.The sub-sectoral analysis of reveals that exchange rate regimes over the years have neither produced the desired results of enhancing agricultural exports nor manufactured exports. This suggests that exchange rate policy has discouraged manufactured exports because its production highly depends on imported inputs. The policy implication of the above findings is that there is need to achieve an equilibrium exchange rate that when combined with export incentives will promote non-oil exports in Nigeria. Keywords: Trade, Exchange rate, Manufacturing sector, Agricultural sector JEL Classifications: C22, E22, F13, F31, O14, O24